1992
DOI: 10.1002/mus.880150215
|View full text |Cite
|
Sign up to set email alerts
|

Amyotrophic lateral sclerosis (ALS): A phylogenetic disease of the corticomotoneuron?

Abstract: It is proposed that the primary cell involved in amyotrophic lateral sclerosis (ALS) is the corticomotoneuron. The spinal motoneuron becomes affected as a result of antegrade effects. This hypothesis does not negate most of the presently popular theories regarding the pathogenesis of ALS, but directs focus to one cell type--the corticomotoneuron. It takes cognizance of the complex, monosynaptic, corticomotoneuronal-spinomotoneuronal connections that have evolved in primates, and especially in man. It might exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
120
0
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 212 publications
(124 citation statements)
references
References 64 publications
2
120
0
1
Order By: Relevance
“…A wide range of factors are likely to contribute to ALS pathogenesis, including mitochondrial dysfunction, protein misfolding/aggregation, oxidative damage, neuronal excitotoxicity, non-cell-autonomous effects/neuroinflammation, axonal transport defects, neurotrophin depletion, effects from extracellular mutant SOD1, and aberrant RNA processing (Eisen et al, 1992;Chou and Norris, 1993;Williamson, 1999;Kieran et al, 2005;De Winter et al, 2006;Parkhouse et al, 2008;Schmidt et al, 2009;Bilsland et al, 2010;Brockington et al, 2010;Li et al, 2010;Dadon-Nachum et al, 2011). However, the extent to which each factor is involved and the overall pathology of the disease are still not understood.…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of factors are likely to contribute to ALS pathogenesis, including mitochondrial dysfunction, protein misfolding/aggregation, oxidative damage, neuronal excitotoxicity, non-cell-autonomous effects/neuroinflammation, axonal transport defects, neurotrophin depletion, effects from extracellular mutant SOD1, and aberrant RNA processing (Eisen et al, 1992;Chou and Norris, 1993;Williamson, 1999;Kieran et al, 2005;De Winter et al, 2006;Parkhouse et al, 2008;Schmidt et al, 2009;Bilsland et al, 2010;Brockington et al, 2010;Li et al, 2010;Dadon-Nachum et al, 2011). However, the extent to which each factor is involved and the overall pathology of the disease are still not understood.…”
Section: Discussionmentioning
confidence: 99%
“…6 Some have suggested that ALS is primarily an upper motor neuron (UMN) disorder with secondary anterograde degeneration ("dying forward") of the lower motor neuron (LMN) [7][8][9] ; others have postulated a retrograde ("dying back") process in which pathology begins in the LMN. 10 Within the last few years, 2 related ideas about disease onset and progression have emerged.…”
Section: Rationale Disease Biologymentioning
confidence: 99%
“…The reported degeneration of the dendritic arborizations, changes in synapses, and loss of Betz cells in amyotrophic lateral sclerosis and other degenerative illnesses involving the primary motor cortex suggest a participation of this neuronal subpopulation in the process of the disease (Hammer et al, 1979;Udaka et al, 1986;Kiernan and Hudson, 1991;Murayama et al, 1992;Nimchinsky et al, 1992;Nihei et al, 1993;Sasaki and Murayama, 1994;Pamphlett et al, 1995;Fujita et al, 1999;Sasaki and Iwata, 1999;Tsuchiya et al, 2000Tsuchiya et al, , 2002Hof and Perl, 2002). The hypothesis that spinal motoneuronal degeneration is secondary to cortical transynaptic degeneration (Eisen et al, 1992), even if widely criticized (Pamphlett et al, 1995), has refocused attention on the possible involvement of the primary motor cortex in lower motoneuron disease. Many authors have attempted to establish a relation between neuronal loss and shrinkage in the spinal cord and in large motoneurons in the primary motor cortex (Marie, 1928;Davison, 1941;Lawyer and Netsky, 1953;Kiernan and Hudson, 1991;Nihei et al, 1993;Pamphlett et al, 1995) by comparing neuronal size between pathologic and control cases and quantifying the total number of motoneurons in different cortical and spinal regions.…”
Section: Betz Cells Neurodegenerative Diseases and Normal Brain Agingmentioning
confidence: 99%